2019
DOI: 10.1208/s12248-019-0313-2
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Concentrations of Budesonide and Fluticasone Propionate: a Study in Mice

Abstract: The study goal was to evaluate the transplacental transfer of two corticosteroids, budesonide (BUD) and fluticasone propionate (FP), in pregnant mice and investigate whether P-glycoprotein (P-gp) might be involved in reducing BUD transplacental transfer. Pregnant mice (N = 18) received intravenously either low (104.9 μg/kg) or high (1049 μg/kg) dose of [ 3 H]-BUD or a high dose of [ 3 H]-FP (1590 μg/kg). In a separate experiment, pregnant mice (N = 12) received subcutaneously either the P-gp inhibitor zosuquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Data from large-scale retrospective studies have shown that treatment with anti-asthmatic medications can increase the risk of pregnancy complications and low infant birth weight [147, 148], although budesonide-specific data have not shown a significant increase in congenital malformations [39, 149]. A study in pregnant mice showed less transplacental transfer of free budesonide than of free FP [150]. This appeared to depend on the lower lipophilicity of budesonide and the fact that, as a substrate for P-glycoprotein, budesonide can be transported out of the placenta and brain.…”
Section: Safetymentioning
confidence: 99%
“…Data from large-scale retrospective studies have shown that treatment with anti-asthmatic medications can increase the risk of pregnancy complications and low infant birth weight [147, 148], although budesonide-specific data have not shown a significant increase in congenital malformations [39, 149]. A study in pregnant mice showed less transplacental transfer of free budesonide than of free FP [150]. This appeared to depend on the lower lipophilicity of budesonide and the fact that, as a substrate for P-glycoprotein, budesonide can be transported out of the placenta and brain.…”
Section: Safetymentioning
confidence: 99%